The origin of the Proto-Indo-European comparative suffix (with Turkic and Uralic parallels) - Szeptyński, Rafał (Lingua Posnaniensis, 2018)
The article deals with the origin of the Proto-Indo-European comparative suffix. It is claimed that the morpheme in question, reconstructed here as *-i̯ōs < *-i̯o-os, evolved in predicatively used *-s-stem nominals. It is also claimed that the first component of the complex *-i̯o-os is the allomorph *-i̯o- of the verbal suffix *-i̯e/o-. Both intrasystemic and typological parallels indicate that the verbal component could originate from intransitive change-of-state verbs. It is suggested that the ablaut varieties of the comparative suffix and the frequent predesinential extensions are due to independent inflectionalization in various post-Proto-Indo-European dialects.